Assessment of the prevalence of radix entomolaris and distolingual canal in mandibular first molars in 15 countries: a multinational cross-sectional study with meta-analysis - Hatipoglu, Fatma Pertek; Magat, Guldane; Hatipoglu, Omer; Al-khatib, Hanan; Elatrash, Anas S; Zainal Abidin, Imran; Kulczyk, Tomasz; Ahmed Mohamed Alkhawas, Moataz-Bellah; Buchanan, Glynn Dale; Kopbayeva, Maira; Surendar, Sugumaran; Javed, Muhammad Qasim; et al. (Elsevier, 2023)
Aim: The aim of this study was two-folded: i) to assess the prevalence of Distolingual Canal (DLC) and Radix Entomolaris (RE) in Mandibular First Molars (M1Ms), using Cone Beam Computed Tomography (CBCT) images and ii) to assess the impact of sociodemographic factors on the prevalence of these conditions worldwide.